Analysis of Personal Privacy Risks and Protection Countermeasures under the Privacy Paradox Dimension - Li, Tingjing (Transactions on Social Science, Education and Humanities Research, 2024)
The privacy paradox is an important issue facing the current digital age, which involves a contradiction between individuals’ perceptions of privacy protection and their actual behavior. Despite the general awareness of privacy risks, voluntary disclosure of personal data on digital channels such as social media platforms are still prevalent. This dissertation aims to explore the nature of personal privacy risk under the dimension of privacy paradox and the strategies to deal with it. By analyzing the definition, manifestation and influencing factors of the privacy paradox, combined with the problems and causes brought by personal privacy exposure, this paper proposes protection countermeasures in multiple dimensions, such as legal policies, industry self-regulation, technological means and personal behaviors. With the continuous development and popularization of digital technology, the challenge of personal privacy protection is becoming increasingly severe, but through the comprehensive use of various means and measures, the risks brought about by privacy leakage can be effectively counteracted and personal privacy security can be protected.